ANALISIS LIMITASI LOCUS DAN TEMPUS DELICTI DALAM DELIK PENIPUAN YANG TERJADI DI LUAR NEGERI (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 58/PK/PID/2018) - Philbert Audric Deigo; Dian Adriawan DG Tawang (Jurnal Hukum Adigama, 2020)
This studies discuses the Analysist Limitation Location and Time of Fraud that Occurred Outside Indonesia using Supreme Court Verdict Number 58/PK/PID/2018 as the material of studies. Problem that arises is how does limitaion location and time of criminal act works if someone commit crime outside of Indonesia’s Juridiction? Investigator have to comprehend these two contituents because it’s a critical element that’s drive the criminal procedural law. In this era of technology fraud can be nowhere near the victims, therefore investigation going to take more effort and time. Investigator as the Government’s representative must have understood the principle in crime from all angle of aspect. Government especially diplomatic part must have realized this problem and have it solved a long time ago by proposing bilateral agreements to those country that have potential to become locus and tempus of criminal act, because the process take years only for ordinary fraud case that’s not have any complexity at all.